High mortality among patients hospitalized for drug‐resistant tuberculosis with acquired second‐line drug resistance and high HIV prevalence. Issue 10 (24th May 2022) - Anderson, Kim; Pietersen, Elize; Shepherd, Bryan E.; Bian, Aihua; Dheda, Keertan; Warren, Robin; Sterling, Timothy R.; van der Heijden, Yuri F.
Abstract: Objectives: We compared mortality between HIV‐positive and HIV‐negative South African adults with drug‐resistant tuberculosis (DR‐TB) and high incidence of acquired second‐line drug resistance. Methods: We performed a retrospective review of DR‐TB patients with serial second‐line TB drug susceptibility tests (2008–2015) who were hospitalized at a specialized TB hospital. We used Kaplan–Meier analysis and Cox models to examine associations with mortality. Results: Of 245 patients, the median age was 33 years, 54% were male and 40% were HIV‐positive, 96% of whom had ever received antiretroviral therapy (ART). At initial drug resistance detection, 99% of patients had resistance to at least rifampicin and isoniazid, and 18% had second‐line drug resistance (fluoroquinolones and/or injectable drugs). At later testing, 88% of patients had acquired additional second‐line drug resistance. Patient‐initiated treatment interruptions (> 2 months) occurred in 47%. Mortality was 79%. Those with HIV had a shorter time to death ( p = 0.02; log‐rank): median survival time from DR‐TB treatment initiation was 2.44 years [95% confidence interval (CI): 2.09–3.15] versus 3.99 years (95% CI: 3.12–4.75) for HIV‐negative patients. HIV‐positive patients who received ART within 6 months before DR‐TB treatment had a higher mortality hazard than HIV‐negative patients [adjusted hazard ratio (aHR) ratio = 1.82, 95% CI: 1.21–2.74]. By contrast, HIV‐positive patients who did not receive ART within 6 months before DR‐TB treatment did not have a significantly higher mortality hazard than HIV‐negative patients (aHR = 1.09; 95% CI: 0.72–1.65), although those on ART had lower median CD4 counts than those not on ART (157 vs. 281 cells/μL, respectively; p = 0.02). Conclusions: A very high incidence of acquired second‐line drug resistance and high overall mortality were observed, reinforcing the need to reduce the risk of acquired resistance and for more effective treatment.